ECONOMIC DEVELOPMENT OF COUNTRIES IN A STATE OF ARMED CONFLICT: AN ARMENIAN CASE-STUDY - MARKOSIAN, Ashot; AVAKIAN, Boris; MATEVOSIAN, Elianora (CENTRAL ASIA AND THE CAUCASUS, 2013)
This article takes a look at the current state and dynamics of Armenia’s economy over the past few years. The authors have studied several budget expenditure items and conducted a comparative analysis of Armenia’s external trade indices with the countries of the region. Involvement in any conflict, particularly one that is unresolved, has an impact on the country’s economy and makes it unattractive to investors, who do not like vagueness and avoid risks; commerce strives to minimize transactional outlays, while closed borders lead to enclave development. This is precisely how Armenia’s economy has been developing over the past two decades.This situation is making the country’s economy dependent on particular players, different factors, and so on, leading to monopolization of its main branches and underdevelopment of sectors that, under other conditions, could become a catalyst for economic progress. An analysis of the economic growth trends in the Republic of Armenia (RA) shows that this growth is still having little influence on the standard of living of the country’s population, since government budget expenditures are mainly oriented toward defense. At the same time, the main source of personal monetary income comes from private remittances.Investment flows and Armenia’s reciprocal trade with neighboring countries are going against the overall economic integration trends. This is causing countries that are already in a state of conflict to move increasingly away from each other. The authors of this article believe that economic cooperation among all the countries of the Southern Caucasus should become an alternative to the continuing conflict.